Assessing the epidemiological effect of wolbachia for dengue control. Issue 7 (July 2015) - Lambrechts, Louis; Ferguson, Neil M; Harris, Eva; Holmes, Edward C; McGraw, Elizabeth A; O'Neill, Scott L; Ooi, Eng E; Ritchie, Scott A; Ryan, Peter A; Scott, Thomas W; Simmons, Cameron P; Weaver, Scott C
Summary Dengue viruses cause more human morbidity and mortality than any other arthropod-borne virus. Dengue prevention relies mainly on vector control; however, the failure of traditional methods has promoted the development of novel entomological approaches. Although use of the intracellular bacterium wolbachia to control mosquito populations was proposed 50 years ago, only in the past decade has its use as a potential agent of dengue control gained substantial interest. Here, we review evidence that supports a practical approach for dengue reduction through field release of wolbachia-infected mosquitoes and discuss the additional studies that have to be done before the strategy can be validated and implemented. A crucial next step is to assess the efficacy of wolbachia in reducing dengue virus transmission. We argue that a cluster randomised trial is at this time premature because choice of wolbachia strain for release and deployment strategies are still being optimised. We therefore present a pragmatic approach to acquiring preliminary evidence of efficacy through various complementary methods including a prospective cohort study, a geographical cluster investigation, virus phylogenetic analysis, virus surveillance in mosquitoes, and vector competence assays. This multipronged approach could provide valuable intermediate evidence of efficacy to justify a future cluster randomised trial.